Monitoramento terapêutico do 5-fluorouracil como ferramenta clínica de avaliação no tratamento de pacientes com câncer do trato gastrointestinal - Baco, Lucas Silva de (2023)
5-fluorouracil (5-FU) is an essential part of the treatment of numerous solid cancers, especially of the gastrointestinal tract (GI tract). Despite the many advances related to its use, some patients undergoing 5-FU therapy exhibit severe toxicity. Recent studies indicate that the severe toxicity may be related to a reduced activity of the enzyme dihydropyrimidine dehydrogenase (DPD), involved in the clearance of the drug, caused mainly by polymorphisms in the gene encoding DPYD. The dose of 5-FU is determined by anthropometric parameters, and there is a wide interindividual variability of exposure. The objective of this study was to evaluate the use of therapeutic monitoring of 5-FU as a possible clinical tool to reduce toxicity and improve the therapeutic goal in patients with GIT cancer, through the study of DPYD genotyping, DPD phenotyping and determination of the plasma area under the curve (AUC) of 5-FU. We evaluated 47 patients of both sexes with gastrointestinal cancer being treated at Santa Maria University Hospital, receiving 5-FU-based therapeutic regimens. 5-FU quantification and DPD phenotyping were performed by UPLC-MS/MS. DPYD genotyping was performed using the QIAamp DNA Mini Kit (QIAGEN). Common Terminology Criteria for Adverse Events (CTCAE) was used for grading toxicities. Forty-seven patients were included in the study. The mean age was 64.26±10.72 years. The most frequent cancers were colon (27.65%) and stomach (25.53%). The main therapeutic regimen used was FOLFOX/mFOLFOX6 (85.10%). For hematological toxicities, 25.53% of patients had some degree of neutropenia, 89.36% anemia, and 27.65% thrombocytopenia. There were Grade III/IV occurrences for neutropenia and anemia and Grade III for thrombocytopenia. The AUC of 5-FU, calculated from plasma concentration, was evaluated for 3 treatment cycles, it was observed that at the initial cycle (C1) 48.93% were underexposed and 10.63% overexposed, a total of 59.56% of patients outside the therapeutic range (20-30 mg.h/L). For intraindividual variability 69.23% of patients had a delta ratio less than 0.05, demonstrating low intraindividual variability. For DPYD genotyping, 97.87% of patients had a wild-type genotype and 2.12% a heterozygous mutation for c.1236G>A (E412E, rs56038477). For the DPD phenotype, 82.97% of patients had a phenotype compatible with normal activity and 17.02% a phenotype compatible with partial enzyme deficiency. Our results demonstrate that a set of assessments: DPYD genotyping, DPD phenotyping and, above all, the plasma AUC of 5-FU, can indeed contribute in clinical routine. Although in our group of patients the relationship with genotyping and phenotyping as a predictive approach to toxicity has not been well established, AUC in turn was essential in identifying patients who were outside the therapeutic range considered adequate (20-30 mg.h/L). In this sense, the importance of therapeutic monitoring of 5-FU to maintain the appropriate therapeutic range and avoid possible toxicities is highlighted.